An Inquiry Into the Effect of Working Capital Management on Firm Performance Using a Combined Approach of Bibliometric and Thematic Analysis - Bhatt, Amola; Mehta, Bhoomi; Raval, Avani; Joshi, Nisarg (Copernican Journal of Finance & Accounting, 2025)
The current study evaluates the existing literature to understand the evolving nature of the relationship between a firm’s short-term financial decisions and its performance. This paper aims to understand the knowledge progression and its present status, and identify future research directions. The study achieves this by looking at the existing research through an integrated lens of bibliometric analysis and thematic literature review. The findings of bibliometric analysis reveal the most influential works and authors in the domain and discuss the conceptual and intellectual structure of working capital and its impact. Through the thematic analysis, the existing literature has been analysed by grouping them under four major themes. Based on the findings, the current research gaps have been identified and the study has suggested the future research direction.